« A Shadow behind the Heart » : l’Étranger au cœur de l’intime dans Pnin de Nabokov - Lara Delage-Toriel (Revue LISA)
According to Nabokov, the writer’s one and only passport is his style, which allows him to cross and especially transcend any geopolitical boundary. For all that, strangers and foreigners are frequently present in his work. One may even say they haunt every one of his novels and stories, especially Pnin, in which the eponymous hero most vibrantly embodies that concept coined by the Russian Formalists, ostranenie, “making strange”. The present article will explore the essential strangeness which at once constitutes the external shell of the character and informs his deepest inner self, like the “shadow behind the heart” of Pnin that appears in X-rays yet evades all medical explanation. So how does Nabokov succeed in making the reader sense the foreigner’s condition without depriving it of its edge, its aura of strangeness? How can he make us grasp what must usually evade definition? How does his writing achieve this double-bind, making us experience foreignness from the inside as well as the outside?